Análisis de roles periodísticos en la redacción de noticias de periódicos locales sobre casos de femicidio en El Oro, 2019 - Macías Neira, Marilyn Yaritza (Machala, 2020)
This investigation was conducted to learn how the media treats information related to femicide cases which occurred in 2019, for this purpose, was used as an object of study to the three local newspapers that are sold in the city of Machala which are: The National, Opinión and Correo. These three journals were used to know all the notes that were disseminated about femicide cases and by obtaining them was made a content analysis to analyze what professional journalistic role the journalist assumed at the time of writing the news event, and to do this, a matrix was used in which it explains each of the characteristics of the classification of journalistic professional roles, in addition to interpret what kind of note it is and what factors depend on to assign the space for every news story. A methodology with a qualitative approach was used with the use of three techniques: bibliographic review, content analysis and interviews. Four types of roles were used for the content analysis, the interventionist, the infoentretenimnto, the service and the civic, and to contrast the information obtained from the media, the information provided by the people who were interviewed will be used, in this case the journalists who drafted the notes of some femicide case that occurred last year.
La presente investigación se llevó a cabo para conocer cómo los medios de comunicación tratan la información relacionada con los casos de femicidio que ocurrieron en el año 2019, para ello, se utilizó como objeto de estudio a los tres diarios locales que se venden en la ciudad de Machala que son: El Nacional,Opinión y Correo. Estos tres diarios se utilizaron para conocer todas las notas que se difundieron sobre los casos de femicidio y mediante la obtención de las mismas se realizó un análisis de contenido para identificar qué rol profesional periodístico asumió el comunicador al momento de redactar el hecho noticioso. Para ello, se utilizó una matriz en donde se explica cada una de las características de la clasificación de los roles profesionales periodísticos, además se identificó el tipo de nota y los factores que influyen para asignarle el espacio a cada noticia. Se utilizó una metodología con un enfoque cualitativo con el uso de tres técnicas: revisión bibliográfica, análisis de contenido y entrevistas. Para el análisis de contenido se utilizaron cuatro tipos de roles, el intervencionista, el infoentretenimnto, el de servicio y el cívico, y para contrastar la información obtenida de los medios se utilizó la información brindada por los entrevistados; es decir, los periodistas que redactaron las notas sobre algún caso de femicidio que ocurrió el año pasado.
Keywords: CASOS DE FEMICIDIO; ROLES PROFESIONALES PERIODÍSTICOS, CRÓNICA ROJA.